Concepções de ensino e práticas pedagógicas de professores no contexto das salas de aula multianuais/multisseriadas de escolas do/no campo - Silva, Joseildo Silvestre da (2023)
The teachers' conceptions of teaching can contribute to the pedagogical processes, in particular the practices that are conducted in the classroom. Thus, the present research aims at investigating the teaching conceptions that permeate the pedagogical practices of teachers of multiyear/multigrade classrooms of schools from the countryside. In relation to the methodology, this research was characterized as descriptive and field research, of a qualitative nature and we used, as instruments for data collection, semi-structured interviews and systematic observation. Regarding the research sample, for convenience, we selected as research collaborator three teachers who work in multi-year/multi-grade classrooms in the rural area schools, teaching the early years of elementary school in the municipality of Jucurutu/RN. Thus, the practice of the research collaborating professors was observed and their speeches were collected through interviews in order to gather answers to the problem question. To analyze the data obtained, the technique of document analysis and content analysis were used. Through document analysis, the Municipal Education Plan – PME and the Pedagogical Political Project (PPP) of the rural center that encompasses the schools that were the focus of the study, an analysis of some excerpts from the collaborating teachers' lesson plans was also carried out. The content analysis allowed us to perceive through the speeches/voices of the collaborators points and interpretative lines for, associating the observations and analysis of documents, to trace reflections for the object of study. In view of the research carried out, it was pointed out as findings that the pedagogical practices of teachers are permeated by more than one conception of teaching, such as the traditional, cognitive and socio-cultural ones, but predominantly the cognitive and socio-cultural stand out in relation to the others and that these provide contributions for the alignment of the teacher's pedagogical work. However, there is a need for these conceptions to be better discussed and assimilated in the context of multiannual/multiserial classrooms in/in the countryside. It was concluded that teaching conceptions contribute to the theory-practice relationship that is so necessary in teaching, as they establish a complementary relationship in which practices provide elements to discuss and expand theory and, on the other hand, theory offers subsidies to critically reflect on practice, helping to improve it.